POLITENESS ISSUES IN COMMUNICATION OVER TEXT MESSAGES - Made Frida Yulia (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Text messages have become common media of communication in this era. Face-to-face interactions between teachers and students have often been replaced by virtual communication through these media. In practice, such a communication may create breakdown due to the language which is used in them. Politeness features which serve an essential buffer for a successful interaction are sometimes neglected. The research was aimed at analyzing politeness issues appearing in English and Indonesian text messages. The communication took place between Indonesian students at the English Education Department of Sanata Dharma University Yogyakarta and their teachers. Thirty text messages were collected from various teachers and then they were analyzed. The analysis revealed that there were features in the text messages which did not abide by the principles of politeness. It could be seen among others from the diction and absence of greetings and address terms. The situation was potentially able to induce discomfort on the receiver’s part and it may affect the flow and success of communication. From the findings it could be concluded that not all of the senders had sociolinguistic competence. Such senders often disregarded the concepts of social distance and power relation, which should actually be taken into consideration while texting their teachers.